The Sustainability of Nuclear Fuel Resources in Indonesia with Open and Closed Fuel Cycle - Dwijayanto, R. Andika Putra (Sustainability Science and Resources, 2023)
In the wake of climate change and global warming, various alternatives are being considered as a potential replacement for fossil fuels. Despite often being overlooked, nuclear power offers many benefits as a low-carbon energy source. Being a thermal power plant, nuclear power can generate energy reliably without relying on weather without emitting greenhouse gases during its operation. Serialised construction can reduce the capital cost, which often touted as expensive. Due to the commitment to the Paris Protocol, Indonesia is obliged to achieve carbon neutrality in its energy generation, and nuclear power is a plausible option to replace fossil fuel generation. One of the questions regarding nuclear power deployment in Indonesia is the sustainability of the nuclear fuel, especially considering its domestic resources both uranium and thorium. This study estimates how long uranium and thorium resources in Indonesia will last when used to power the nuclear power plants with open and closed fuel cycles. Several reactor designs were considered. The calculation result shows that domestic nuclear fuel resources in Indonesia can be sustainable enough, provided that closed nuclear fuel cycle is deployed.